1997
DOI: 10.1006/jabr.1996.6811
|View full text |Cite
|
Sign up to set email alerts
|

Finite core-pp-groups

Abstract: Forna positive integer, a groupGis calledcore-nifH/H Ghas order at mostnfor every subgroupHofG(whereH Gis the normal core ofH, the largest normal subgroup ofGcontained inH). It is proved that a finite core-pp-groupGhas a normal abelian subgroup whose index inGis at mostp 2ifpâ� 2, which is the best possible bound, and at most 2 6ifp=2. © 1997 Academic Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…Subgroups of Q are core-free, and if jQj > p, then Q has a 2-generated subgroup of order greater than p, a contradiction. Another equivalent characterisation of core-p-ness may be found in [3,Lemma 1.3]: The group G enjoys core-p-ness if and only if every nontrivial subgroup H of G has a maximal subgroup M with OEM; G Ĉ.H /.…”
Section: B Wilkensmentioning
confidence: 99%
See 3 more Smart Citations
“…Subgroups of Q are core-free, and if jQj > p, then Q has a 2-generated subgroup of order greater than p, a contradiction. Another equivalent characterisation of core-p-ness may be found in [3,Lemma 1.3]: The group G enjoys core-p-ness if and only if every nontrivial subgroup H of G has a maximal subgroup M with OEM; G Ĉ.H /.…”
Section: B Wilkensmentioning
confidence: 99%
“…A group G is called core-n if jH=H G j Ä n for every subgroup H of G; here, H G denotes the largest normal subgroup of G contained in H . In [4], it was shown that a locally finite core-n group has a normal abelian subgroup whose index in the group is bounded by a function of n. In [3] the same authors proved that, for odd primes p, a finite core-p p-group has an abelian normal subgroup of index p 2 , a best possible bound. The paper ( [3,Theorem 2]) also contains a proof of the existence of a normal abelian subgroup of index at most 2 6 in a finite core-2 2-group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [2], Lennox, Smith and Wiegold show that, for p = 2, a core-p p-group is nilpotent of class at most 3 and has an abelian normal subgroup of index at most p 5 . Furthermore, Cutolo, Khukhro, Lennox, Wiegold, Rinauro and Smith [3] prove that a core-p p-group G has a normal abelian subgroup whose index in G is at most p 2 if p = 2. Furthermore, if p = 2, Cutolo, Smith and Wiegold [4] prove that every core-2 2-group has an abelian subgroup of index at most 16.…”
Section: Introductionmentioning
confidence: 99%